High-accuracy approximation of effective coefficients - Neuß, Nicolas (Reactive flows, diffusion and transport, 2007)
In this contribution we study the calculation of effective coefficients for media with periodic heterogeneities. We use finite element methods of high order which allows to obtain high accuracy with relatively low computational effort. This is shown both theoretically and practically.